2020
DOI: 10.1111/psyp.13539
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical fitness parameters and white matter microstructure in older adults: A diffusion tensor imaging study

Abstract: The present study was designed to examine whether different measures of physical fitness are differentially associated with white matter (WM) microstructure in older adults. Fifty-six healthy adults (mean age: 59.14 years) completed a standardized evaluation of physical fitness measurements (e.g., VO 2peak , push-ups, abdominal situps, sit-and-reach, t test, and vertical jump). Fractional anisotropy (FA), an index of WM microstructure, was assessed using diffusion tensor imaging. The findings indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
1
3
0
5
Order By: Relevance
“…These findings demonstrate the beneficial effects for WM integrity associated with higher levels of aerobic fitness. Consistently, in our cross-sectional sample of late middle-aged adults (55-65 years), a positive association between aerobic fitness (VO 2peack ) and the FA value in the left cerebral peduncle was previously reported (Chen et al, 2020a). Previous studies have reported that several brain regions are sensitive to aerobic fitness, including the cingulum bundle, the corpus callosum, the anterior internal capsule, the fornix, and the anterior corona radiata (Johnson et al, 2012;Tseng et al, 2013;Hayes et al, 2015;Oberlin et al, 2016), and the present findings expand these associations to other regions, especially the cerebral peduncle and the uncinate fasciculus.…”
Section: Discussionsupporting
confidence: 90%
“…These findings demonstrate the beneficial effects for WM integrity associated with higher levels of aerobic fitness. Consistently, in our cross-sectional sample of late middle-aged adults (55-65 years), a positive association between aerobic fitness (VO 2peack ) and the FA value in the left cerebral peduncle was previously reported (Chen et al, 2020a). Previous studies have reported that several brain regions are sensitive to aerobic fitness, including the cingulum bundle, the corpus callosum, the anterior internal capsule, the fornix, and the anterior corona radiata (Johnson et al, 2012;Tseng et al, 2013;Hayes et al, 2015;Oberlin et al, 2016), and the present findings expand these associations to other regions, especially the cerebral peduncle and the uncinate fasciculus.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, FA in the left cingulum partially mediated the relationship between cardiorespiratory fitness and spatial working memory, suggesting that WM integrity is a critical component in the relationship between cardiorespiratory fitness and elevated spatial memory performance. In healthy midlife to older adults, higher cardiorespiratory fitness was associated with higher FA in the right hippocampal segment of the cingulum and the left cerebral peduncle (F.-T. Chen, Erickson, et al, 2020). Similarly, in a sample of 15 older adults, Marks et al (2011) found that cardiorespiratory fitness explained 28.5% of the variance in FA in the left cingulum.…”
Section: Wm Microstructurementioning
confidence: 93%
“…In healthy midlife to older adults, higher cardiorespiratory fitness was associated with higher FA in the right hippocampal segment of the cingulum and the left cerebral peduncle (F.‐T. Chen, Erickson, et al, 2020). Similarly, in a sample of 15 older adults, Marks et al (2011) found that cardiorespiratory fitness explained 28.5% of the variance in FA in the left cingulum.…”
Section: Hippocampal Wmmentioning
confidence: 99%
“…Lifestyle factors have been more extensively studied in relation to dMRI outcomes without uncovering pathways between them. Using dMRI data on 56 healthy individuals, a study detected changes in hippocampus connected to cardiopulmonary fitness ( Chen et al, 2020 ). Using data from the Multidomain Approach for Preventive Trial phase III, researchers found that physical activity levels influence the white matter integrity, ( Maltais et al, 2020 ) findings corroborated by another recent study of healthy subjects ( Bashir et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%